The Role of Spiritual Guidance on the Emotional Stability of People with Mental Disorders (ODGJ) in the Sumedang Bina Laras Service Unity - Nindy Aprianie; Yandi Cahya Yundani; Yudi Guntara; Iwa Budiana (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study aims to analyze the role of spiritual guidance in improving the emotional stability of people with mental disorders (ODGJ) at the Bina Laras Sakurjaya Service Unit in Sumedang. The research employed a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation. The informants included a spiritual counselor, client assistants, the head of the social service center, and administrative staff. The findings reveal that spiritual guidance is implemented in a structured manner through activities such as congregational prayer, dhikr, Qur’an recitation, sholawat, yasinan, and manaqib, complemented by individual and group counseling sessions. These activities are carried out using a persuasive approach adjusted to the psychological conditions of the clients. The emotional condition of clients, which was initially unstable, gradually improved after participating in regular spiritual activities, as indicated by increased calmness, better emotional control, and improved social interaction. Spiritual guidance serves as a non-medical therapeutic approach that provides inner peace, reduces anxiety, and helps clients develop meaning in life and hope. Therefore, spiritual guidance plays a significant role in supporting the rehabilitation process and enhancing the emotional stability of individuals with mental disorders.